The joy of achievement : conversations with J.R.D. Tata - Lala, R.M. (b, 1995)
An entertaining, intimate and deeply moving portrait of the legendary industrialist. For six decades J.R.D. Tata headed India's largest industrial conglomerate with uncommon success. This was only one aspect of his life. He was also a man of great sensitivity who suffered at the loss of friends and was pained by the poverty he saw around him: a philanthropist who wanted India to be -a happy country' and did all that he could to make it so: a man with a passion for literature, fast cars, skiing and, of course, flying. This book, by the author of the best-selling The Last Blue Mountain, records JRD's thoughts on a variety of subjects. In these pages he speaks of the House of Tatas and his style of management, about how he nearly joined the freedom struggle in the early 1940s, about the -thrill of living a little dangerously', his love of music and wine, and the writers he likes to read. He speaks also, with striking candour and insight, about the failures of socialism, the future of India and his association with stalwarts like Jawaharlal Nehru. Jayaprakash Narayan, Vallabbhai Patel, Indira Gandhi and Henry Kissinger. Towards the end of the book, in the final year of his life, we see him come to terms with death, God and the afterlife.
Includes index.
Keywords: Industrial policy -- India